Knowledge of HPV Among United States Hispanic Women: Opportunities and Challenges for Cancer Prevention - KOBETZ, ERIN (2010)
In the United States, Hispanic women contribute disproportionately to cervical cancer incidence and mortality. This disparity, which primarily reflects lack of access to, and underutilization of, routine Pap smear screening may improve with increased availability of vaccines to prevent Human Papillomavirus (HPV) infection, the principal cause of cervical cancer. However, limited research has explored known determinants of HPV vaccine acceptability among Hispanic women. The current study examines two such determinants, HPV awareness and knowledge, using data from the 2007 Health Interview National Trends Survey (HINTS) and a cross-section of callers to the National Cancer Institute’s (NCI) Cancer Information Service (CIS). Study data indicate that HPV awareness was high in both samples (69.5% and 63.8% had heard of the virus) but that knowledge of the virus and its association with cervical cancer varied between the two groups of women. The CIS sample, which was more impoverished and less acculturated than their HINTS counterparts, were less able to correctly identify that HPV causes cervical cancer (67.1% vs. 78.7%) and that it is a prevalent sexually transmitted infection (STI; 66.8% vs. 70.4%). Such findings imply that future research may benefit from disaggregating data collected with Hispanics to reflect important heterogeneity in this population subgroup’s ancestries, levels of income, educational attainment, and acculturation. Failing to do so may preclude opportunity to understand, as well as to attenuate, cancer disparity.